Do childcare centres understand parents? Looking from the perspective of parent behavioural intention - Nik Syuhailah, Nik Hussin; Zuraimi, Abdul Aziz; Nurul Ashykin, Abd Aziz (Malaysian Association of Consumer and Family Economics (MACFEA), 2022)
This study examines the determinants of parents’ behavioural intention concerning childcare services. The constructs, namely service quality, perceived trust, emotional satisfaction, and behavioural intention were tested. Based on the Stimulus-Organism-Response Theory (SOR) and Expectancy Confirmation Theory (ECT), a mediational model was proposed in this study, which linked service quality with customer behavioural intention via perceived trust and emotional satisfaction. Upon employing a purposive sampling method, this study used survey questionnaires for data collection involving a total of 364 valid questionnaires. Data for this study were analysed using Statistical Package for Social Sciences (SPSS 23) and Partial Least Squares-Structural Equation Modelling (PLS-SEM) Version 3.2.9 to examine the posited research hypotheses. The results reveal that generally all the relationships tested in this study are supported. This study’s results contribute to the consumer behaviour theory and expand the understanding of how childcare providers can sustain in the market. The paper ends with a discussion, implications, limitations, and suggestions for future research.